2017
DOI: 10.1002/mds.27029
|View full text |Cite
|
Sign up to set email alerts
|

PBB3 imaging in Parkinsonian disorders: Evidence for binding to tau and other proteins

Abstract: All PSP patients showed increased retention of the tracer in the basal ganglia, as expected. Binding was also present in asymptomatic SNCA duplication carriers and in an MSA case, which are not typically associated with pathological tau deposition. This suggests the possibility that [ C]PBB3 binds to alpha-synuclein. © 2017 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 36 publications
5
43
0
Order By: Relevance
“…40 One study using the [ 11 C]PBB3 ligand assessed a cohort of PSP-P patients. 41 Similar to the previously mentioned studies, they identified elevated tau uptake in the putamen, midbrain, and globus pallidus compared to controls. However, they did not identify any elevated uptake in dentate nucleus of the cerebellum or thalamus.…”
Section: Parkinson-plus Syndromes Progressive Supranuclear Palsy Syndsupporting
confidence: 80%
See 2 more Smart Citations
“…40 One study using the [ 11 C]PBB3 ligand assessed a cohort of PSP-P patients. 41 Similar to the previously mentioned studies, they identified elevated tau uptake in the putamen, midbrain, and globus pallidus compared to controls. However, they did not identify any elevated uptake in dentate nucleus of the cerebellum or thalamus.…”
Section: Parkinson-plus Syndromes Progressive Supranuclear Palsy Syndsupporting
confidence: 80%
“…Similar patterns of uptake in globus pallidus and midbrain in PSP‐RS have been observed with [ 18 F]THK‐5351, with weaker evidence for cortical uptake . One study using the [ 11 C]PBB3 ligand assessed a cohort of PSP‐P patients . Similar to the previously mentioned studies, they identified elevated tau uptake in the putamen, midbrain, and globus pallidus compared to controls.…”
Section: Parkinson‐plus Syndromessupporting
confidence: 63%
See 1 more Smart Citation
“…[11C]PBB3 PET also showed increased binding in cortical and subcortical regions in a patient with MSA (table 2). 59 Based on matched in vitro fluorescence and autoradiographic binding for PBB3 in the same brain regions, a subset of patients with MSA could be positive because of the high density of GCI in the putamen,60 even though the affinity of PBB3 to α-synuclein is 10–50 times less than that to tau 61. These tau ligands bind to β-pleated sheet secondary structures in tau filaments, which are also characterised by α-synuclein filaments.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…11 C‐PBB3 in PSP showed specific binding in areas where the highest tau burden is expected and was higher in more advanced cases. However, binding was also observed in synucleinopathies, questioning its specificity for tau . In CBD, 11 C‐PBB3 may show specific binding that correlates with the clinical manifestations and asymmetric characteristics of CBS, but further studies are needed.…”
mentioning
confidence: 99%